ChemInform Abstract: Straightforward Synthesis and Antioxidant Studies of Chalcogenoaziridines. Issue 47 (3rd November 2016) - Borges, Rodrigo; Andrade, Floyd C. D.; Schwab, Ricardo S.; Sousa, Fernanda S. S.; de Souza, Maurice Neto; Savegnago, Lucielli; Schneider, Paulo H.
Abstract: Compound (IIIb) shows potential as an antioxidative agent.